Heteroglossia as Practice and Pedagogy
XII, 327 p. 22 illus., 7 illus. in color.
Keywords: This volume presents evidence about how we understand communication in changing times, and proposes that such understandings may contribute to the development of pedagogy for teaching and learning. It expands current debates on multilingualism, asking which signs are in use and in action, and what are their social, political, and historical implications. The volume’s starting-point is Bakhtin’s ‘heteroglossia’, a key concept in understanding the tensions, conflicts, and multiple voices within, among, and between those signs. The chapters provide illuminating accounts of language practices as they bring into play, both in practice and in pedagogy, voices which index students’ localities, social histories, circumstances, and identities. The book documents the performance of linguistic repertoires in an era of profound social change caused by the shifting nature of nation-states, increased movement of people across territories, and growing digital communication. "Our thinking on language and multilingualism is expanding rapidly. Up until recently we have tended to regard languages as bounded entities, and multilingualism has been understood as knowing more than one language. Working with the concept of heteroglossia, researchers are developing alternative perspectives that treat languages as sets of resources for expressing meaning that can be drawn on by speakers in communicatively productive ways in different contexts. These perspectives raise fundamental questions about the myriad of ways of knowing and using language(s). This collection brings together the contributions of many of the key researchers in the field. It will provide an authoritative reference point for contemporary interpretations of ‘heteroglossia’ and valuable accounts of how ‘translanguaging’ can be explored and exploited in the fields of education and cultural studies." Professor Constant Leung, King’s College London, UK.